Konstruksi Gender Pesantren: Gerakan Sosial Santri Sebagai Respon Ajaran Ketidakadilan Gender - Kurniawati, Nurul Qolbi (Asketik: Jurnal Agama dan Perubahan Sosial, 2023)
Students of Salafi Islamic boarding schools who also study at the university be faced with two different areas of knowledge transmission. Knowledge transmission in salafi Islamic boarding schools and knowledge transmission in university which are more inclusive and train critical reasoning. So that it has an impact on the pattern of religious expression of students in the form of rejection of the teachings of gender injustice in the books taught in Islamic boarding schools. This study aims to determine the construction of gender injustice values ​​taught in Islamic boarding schools and how students modify social actions as a form of criticism or response to gender injustice teachings taught in Islamic boarding schools. The method used in this research is qualitative by observing and interviewing students. This study uses Peter L. Berger's theory of social construction to look at the process of constructing and modifying gender-unjust teachings. The results of this study show that the values ​​of gender inequality that are taught are in the form of values ​​that contain the value of treating women such as humiliating women in public spaces and discriminating against women. Then the teaching construction results in modifications to the social actions of the students in the form of: 1) women's cooperation in organization forums 2) proof that women can be leaders 3) active in the women's community as well as campaigns on social media 4) research and writing of scientific papers as a form of disagreement among students on the value of gender inequality in Islamic boarding schools.